Produksi Program Acara “Berkah Islami” di Kompas TV Jawa Tengah (Marketing dan Sponsorship) - Abimanyu Ramadhan P; Djoko Setyabudi (Interaksi Online, 2020)
Television is one of mainstream media which still be the main source of information for a lot of people. As a media which still have a lot of interest in society, competition between tv station to make a good program and having a big rate is still goin on until today. One of the way is by making an islamic program. Berkah Islami is an islamic program which talking about etiqutte and manners in islam, which delivered as an friendly an fun program. Along with it’s talkshow, Berkah Islami also include drama comedy that talks about it’s main discussion in every episode. Airing in Kompas TV Jawa Tengah, Berkah Islami is aired weekly every Sunday, at 05.00WB. In this program which on air since 1st September 2019 until 24th November 2019, from it’s marketing strategy, Berkah Islami is known by 95% post survey’s respondend, and also sponsored by 5 different company with a value of Rp. 6.925.00,-